2019
DOI: 10.15295/bmij.v7i1.1068
|View full text |Cite
|
Sign up to set email alerts
|

Gi̇ri̇şi̇mci̇ Ki̇şi̇li̇k Özelli̇kleri̇ni̇n Gi̇ri̇şi̇mci̇li̇k Ni̇yeti̇ Üzeri̇ne Etki̇si̇: Uygulamali Gi̇ri̇şi̇mci̇li̇k Eği̇ti̇mi̇ne Katilanlar Üzeri̇ne Bi̇r Çalişma

Abstract: Bu çalışmanın amacı, uygulamalı girişimcilik eğitimine katılanların girişimci kişilik özelliklerini ve girişimci kişilik özelliklerinin girişimcilik niyeti üzerindeki rolünü belirlemektir. Araştırma amaçları doğrultusunda tasarlanan ölçme aracında girişimci kişilik özelliklerini belirlemek amacıyla İşcan ve Kaygın (2011) tarafından geliştirilen girişimci kişilik özellikleri ölçeği; girişimcilik niyetini belirlemek amacıyla ise Liñán ve Chen (2009) tarafından geliştirilen girişimcilik niyeti ölçeği kullanılmışt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Also, it has been observed that young people and higher education graduates are ahead of the others in entrepreneurship tendency. Koca, Ballı and Üstün (2019) aimed to determine the entrepreneurial personality traits of those who received applied entrepreneurship training and determine the effect of entrepreneurial personality traits on entrepreneurial intention. According to the study's data, among the entrepreneurial personality traits, it was found that self-confidence was the highest, and the lowest was tolerance to uncertainty.…”
Section: Entepreneurs' Characteristicsmentioning
confidence: 99%
“…Also, it has been observed that young people and higher education graduates are ahead of the others in entrepreneurship tendency. Koca, Ballı and Üstün (2019) aimed to determine the entrepreneurial personality traits of those who received applied entrepreneurship training and determine the effect of entrepreneurial personality traits on entrepreneurial intention. According to the study's data, among the entrepreneurial personality traits, it was found that self-confidence was the highest, and the lowest was tolerance to uncertainty.…”
Section: Entepreneurs' Characteristicsmentioning
confidence: 99%